1999
DOI: 10.1002/aic.690450520
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the sorption of toxic metals on chelant‐impregnated adsorbent

Abstract: IntroductionThe removal of toxic heavy metals such as cadmium, zinc, and lead has become an important concern to manufacturing industries with respect to water purification and wastewater treatment. Several physicochemical technologies have been used for this purpose, including adsorption, ion exchange, and Ž . membrane separation processes Clifford et al., 1986 . Adsorption and ion-exchange processes have been found less expensive than membrane processes for most industrial applications. Most resins have high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 25 publications
0
67
0
Order By: Relevance
“…Various methods, such as precipitation, ion exchange, membrane processes, adsorption, coagulation, flotation, etc., have been applied for the removal of heavy metals from aqueous solution [4][5][6][7]. Some of those processes are often restricted because of technical or economic constraints [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods, such as precipitation, ion exchange, membrane processes, adsorption, coagulation, flotation, etc., have been applied for the removal of heavy metals from aqueous solution [4][5][6][7]. Some of those processes are often restricted because of technical or economic constraints [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen adsorption isotherms (Nova 2200E or Autosorb-1; Quantachrome, Boyton Beach, FL) conducted at -196 o C were used to characterize the physical properties of the GACs, applying the BET equation over the relative pressure range 0.01-0.1 (Lowell et al 2004) to obtain surface areas, and the DFT and BJH equations to ascertain adsorbent pore-size distributions (Tennant and Mazyck 2003). Pore-size distribution replicates indicated differences of no greater than 6% in the pore volume over the range investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ravindran et al (1999) found that pre-adsorbing 8-hydroxyquinoline (oxine) onto Calgon F400 -a bituminous coal-based commercially-available activated carbon -increased the capacity of the carbon towards Cd(II), Zn(II) and Pb(II) ions by at least one order of magnitude. These authors advanced the view that the organic portion of the chelating agent sorbed to the activated carbon through π-π interactions, leaving functional groups available to chelate the aqueous metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many promising techniques in practice to remove heavy metals from water and have already been reported including; precipitation (Esalah et al 2000), flotation (Zouboulis et al 1997), biosorption Ho et al 2001), membrane separation (Canet et al 2002), adsorption on minerals (Buerge-Weirich et al 2002;Ahmed et al 2002;Chamila et al 2015), Zeolites (Pankaj et al 2015) and activated carbon (Khan et al 2015;Ravindran et al 1999). Many researchers also use Bacteria, fungi and algae for removal of heavy metals (Ankur and Chandrajit 2015;Hossein et al 2015).…”
Section: Introductionmentioning
confidence: 99%